MaPep1 and MbPep1, as plant elicitor peptides in banana, confer resistance to banana blood disease caused by Ralstonia syzygii subsp. celebesensis - Praphat Kawicha; Ladawan Rattanapolsan; Ratri Boonruangrod; Yube Yamaguchi; Kusavadee Sangdee; Aphidech Sangdee; Thanwanit Thanyasiriwat (Plant Protection Science)
Peptides play regulatory roles in various plant development and defence processes. They function as molecular messengers that detect threats and trigger defence responses. This study aimed to identify the genes encoding endogenous plant elicitor peptide precursors (PROPEPs) in bananas and their role in inducing resistance to Ralstonia syzygii subsp. celebesensis (Rsc). Two precursor genes, MaPROPEP1 and MbPROPEP1, were discovered and predicted to encode the precursor proteins of elicitor peptides, namely, MaPep1 and MbPep1. Both elicitor peptides contained 23 amino acids of the active elicitor peptide, which activated innate immune responses in banana resistance to Rsc. The disease assessment was conducted by inoculating banana plants with Rsc isolate MY4101 using the root-stabbing method. The results demonstrated that MaPep1 and MbPep1 pretreatment enhanced resistance to banana blood disease, as indicated by reduced disease severity and the absence of wilting for 7 days after infection. The expression of the MaPROPEP1, MbPROPEP1, MaLOX7, and Pr-10 genes was evaluated using qPCR and found to be upregulated by MaPep1 and MbPep1 injection followed by Rsc infection in aboveground banana tissues within 7 days. These findings prove that MaPep1 and MbPep1 are members of the Pep family and exhibit conserved functions across various plant species. This approach may be used to develop strategies for enhancing disease resistance in banana cultivation.